Lithotripsy of Pancreatic Stones in a Patient with Cystic Fibrosis: Successful Treatment of Abdominal Pain - AA Weiss; JM Greig; S Fache (Canadian Journal of Gastroenterology)
Endoscopic pancreatic sphincteroromy and removal of pancreatic stones has been helpful in selected cases of patients with chronic pancreatitis. This article reports the case of an 18-year-old native Indian woman with cystic fibrosis who was experiencing pain related to pancreatitis, complicated by pancreatic duct stricture and lithiasis. Subsequent dilation of the pancreatic stricture and lithotripsy of the pancreatic ductal stones successfully eliminated the abdominal pain